2017
DOI: 10.1080/24733938.2017.1363908
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age and maturity status on the maximum and explosive strength characteristics of elite youth female soccer players

Abstract: 2017) The influence of age and maturity status on the maximum and explosive strength characteristics of elite youth female soccer players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…Generally comparable results showing an influence of predicted maturity status based on predicted maturity offset, i.e., time before or after PHV on absolute values of peak force were noted in a cross-sectional study of 157 female soccer players combined across four competitive age groups, U10 through U16 [49]. However, conclusions based on predicted maturity offset as an indicator of maturity status across this broad age range should be interpreted with caution given limitations of the equation used to predict maturity offset in girls.…”
Section: Discussionmentioning
confidence: 56%
“…Generally comparable results showing an influence of predicted maturity status based on predicted maturity offset, i.e., time before or after PHV on absolute values of peak force were noted in a cross-sectional study of 157 female soccer players combined across four competitive age groups, U10 through U16 [49]. However, conclusions based on predicted maturity offset as an indicator of maturity status across this broad age range should be interpreted with caution given limitations of the equation used to predict maturity offset in girls.…”
Section: Discussionmentioning
confidence: 56%
“…At the elite level, soccer requires high technical ability, tactical awareness, and a high level of physical conditioning (6). Therefore, women's soccer clubs are now investing in youth academies, designed to develop future professional players (10).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Bradley et al (2) reported that players performed better on the Yo-Yo Intermittent Endurance Test Level 2 (YYIEL2) than non-elite players, highlighting the importance of testing and training the ability to sustain high intensity running in female soccer players. Therefore, it is important that the monitoring development of these physical qualities as part of a long term athletic development (LTAD) programme is incorporated into the training programme for youth female soccer players (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study has some limitations requiring consideration. First, we did not control for the maturity status of the participants which could have been relevant as differences in neuromuscular performance have been observed between girls' soccer players after, compared to before their growth spurt [36]. The study sample was restricted to female soccer players aged between 12 and 14 years which limits the generalisation of this study.…”
Section: Discussionmentioning
confidence: 99%